Warmth and Challenge as Common Factors among Eastern and Western Counselors? Buddhist Lamas’ Responses to Western Questionnaires - Elsass1, Peter (International Journal of Psychosocial Rehabilitation, 2017)
Our purpose was to investigate the internal consistency of Western oriented counseling questionnaires in a sample of Tibetan Lamas, and thereafter to investigate these Lamas self-perceptions and practice as spiritual counsellors and thus adding to our understanding of what might be common factors in counseling practice across cultures. A sample of high ranking Tibetan Buddhist Lamas responded to The Five Factor Mindfulness Questionnaire, FFMQ (N= 68), to selected parts of the Development of Psychotherapists Common Core Questionnaire (DPCCQ) (N= 74), and an open-ended questionnaire requesting a description of the Lama’s counseling practice (N= 74). Our study differs from other questionnaire studies foremost by the sample consisting of high ranking Tibetan Lamas doing psychosocial work. With respect to the complexity of Buddhist spiritual counseling, our results nevertheless suggest that counselor relationship styles of ‘warmth’ and ‘challenge’ may be common factors in both Western and Eastern counseling.